2016
DOI: 10.22194/jgiass/4.4.757
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agriculture Loan on Agricultural Farm Productivity: Evidence From District Parachinar, Kurram Agency, Pakistan

Abstract: The present study was designed for the evaluation of the effect of agricultural loan on productivity and income of sample farmers in a backward area of Upper and Lower Kurram tehsil of Parachinar, where the main source of institutional credit is Zarai Taraqiati Bank Ltd (ZTBL). For this purpose, primary data of 100 respondents were collected from two Tehsils i.e. Lower and Upper Kurram by using convenience sampling technique, and multiple regression model was used for data analysis. Furthermore, the research c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The study’s findings revealed the necessity of evaluating current programs of adaptation to increase the resilience of farmers in Pakistan and, more generally, throughout South Asia. The Auto-Regressive Distributed Model was used on time series data (from 1985 to 2015) by Kayani et al ( 2018 ) to calculate the influence of climate change on agriculture in Punjab, Pakistan. It was estimated that increased average temperature and precipitation and two nonclimatic factors, i.e., fertilizer and loan distribution, considerably impact agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…The study’s findings revealed the necessity of evaluating current programs of adaptation to increase the resilience of farmers in Pakistan and, more generally, throughout South Asia. The Auto-Regressive Distributed Model was used on time series data (from 1985 to 2015) by Kayani et al ( 2018 ) to calculate the influence of climate change on agriculture in Punjab, Pakistan. It was estimated that increased average temperature and precipitation and two nonclimatic factors, i.e., fertilizer and loan distribution, considerably impact agricultural production.…”
Section: Introductionmentioning
confidence: 99%